Peningkatan Pengetahuan Lansia Mengenai Tumbuhan Toga untuk Mengatasi Hipertensi di Desa Kampung Besar Kecamatan Teluk Naga: Pengabdian - Siti Robeatul Adawiyah; Teguh Handriyo; Riani Amelia Zahara; Sukmawati Suhendri; Ika Bela; Ika Wahyu Pratiwi; Windiarsih Windiarsih; Dyah Antaria; Sigit Setiawan; Etin Suhartini; Yayah Sorayah; Muhammad Ramadhan; Yohana Aurelya; Anggi Safriyanti; Muhamad Risaldi; Andriansyah Andriansyah; Daeyani Ika Yustianingsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Older adults or the elderly experience a biological process that inevitably occurs in every individual. Hypertension, or high blood pressure, is a condition in which systolic blood pressure is >140 mmHg and diastolic blood pressure is >90 mmHg. A lack of knowledge among older adults and their families regarding toga (family medicinal plants) is a risk factor for delays in detection and management. This community service activity aimed to increase older adults’ knowledge of toga plants through health education. The method used was health education with a pre-test and post-test design involving 30 older adults in Kampung Besar Village, Teluk Naga District. Educational media included presentations, leaflets, and flipcharts on toga plants. The results showed an improvement in the level of knowledge among older adults, with the proportion in the good knowledge category increasing from 20% in the pre-test to 90.5% in the post-test. The conclusion of this activity is that health education is effective in improving older adults’ knowledge of toga plants. It is expected that similar activities can be carried out sustainably by involving families and health cadres.